Epidemiological predictors of quality of life and the role of early markers in children with cerebral palsy: A multi-centric cross-sectional study - Shraddha Badgujar; Jagannath Dixit; Bina M. Kuril; L.S. Deshmukh; Prabha Khaire; Varsha Vaidya; Madhavi Shelke (Pediatrics and Neonatology)
Background: More than 100 million children in the world have at least one type of disability. Among disabled children, approximately 25% of chronic disabilities are of neurological origin. Cerebral Palsy is the leading cause of chronic disability in children, making them not only physically and mentally handicapped but also socially aloof. Methods: This study was conducted among 200 eligible participants from three centers with Child Guidance or Cerebral Palsy clinics in the outpatient department. All the participants were included in the analysis of the epidemiological profile and the role of early markers. Of these, 70 participants were assessed for quality of life according to the age criteria of a pre-tested Cerebral Palsy Quality of Life questionnaire (CP-QOL). Results: Mean ± S.D. age in years was 3.7 ± 2.8. Birth history included 182 (39%) neonatal etiopathology, followed by 173 (38%) perinatal, and 106 (23%) antenatal causes. Mean ± S.D. birth weight was 2.3 ± 1.2 kg. The positive predictors of various domains of Quality of Life were an absence of any associated sensory, neurological, communication, or psychological disorder or disability. While, the negative predictors were decreasing functional capacity, involvement of number of limbs in increasing order, high therapeutic requirements, and dependency. Conclusion: The association between early diagnosis of cerebral palsy and improved functional capacity, involvement of a lesser number of limbs, better quality of life, and absence of associated disabilities is established from the findings of our study.